Hydrophobic and porous carbon nanofiber membrane for high performance solar-driven interfacial evaporation with excellent salt resistance - Zhang, Wei-miao; Yan, Jun; Su, Qin; Han, Jiang; Gao, Jie-feng (Journal of colloid and interface science, 2022)
[Display omitted] •A hydrophobic macro/meso porous carbon nanofiber (HPCNF) membrane is prepared.•The HPCNF exhibits a high sunlight absorption and a large contact angle.•A high interfacial solar evaporation rate is achieved.•The HPCNF has excellent salt-rejection and hence long-term evaporation stability.•Solar desalination can be conducted in high salinity and corrosive conditions. Interfacial evaporation has recently received great interest from both academia and industry to harvest fresh water from seawater, due to its low cost, sustainability and high efficiency. However, state-of-the-art solar absorbers usually face several issues such as weak corrosion resistance, salt accumulation and hence poor long-term evaporation stability. Herein, a hydrophobic and porous carbon nanofiber (HPCNF) is prepared by combination of the porogen sublimation and fluorination. The HPCNF possessing a macro/meso porous structure exhibits large contact angles (as high as 145°), strong light absorption and outstanding photo-thermal conversion performance. When the HPCNF is used as the solar absorber, the evaporation rate and efficiency can reach up to 1.43 kg m−2h−1 and 87.5% under one sunlight irradiation, respectively. More importantly, the outstanding water proof endows the absorber with superior corrosion resistance and salt rejection performance, and hence the interfacial evaporation can maintain a long-term stability and proceed in a variety of complex conditions. The HPCNFs based interfacial evaporation provides a new avenue to the high efficiency solar steam generation.